2021
DOI: 10.1021/acsomega.1c05444
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Design and Syntheses of Porphyrinoids by Embedding Higher Analogues of Arene and Pyridine Units

Abstract: Due to enthralling applications in various fields and augmenting fundamental wisdom, π-conjugated macrocycles in general and porphyrin systems in particular are constantly explored. Subtle modifications of porphyrin structure can amend the rudimentary properties. Pursuing innovative properties provides impetus to underpin arene or pyridine moiety embedded porphyrin derivatives. There have been several reviews related to arene incorporated carbaporphyrinoids; however, recent developments of porphyrin analogues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“… [8] [26]Dioxohexaphyrin(1.1.1.1.1.1) provides a remarkable [NNNO] coordination core, as illustrated by paramagnetic bis‐Cu II compound 3 (Scheme 1) or diamagnetic bis‐Ni II complexes [9] . Incorporation of a pyridine unit into the expanded porphyrin core can be expected to result in specific coordination behaviour [10–13] . Thus, C,G‐di‐pyri‐octaphyrin(1.1.0.0.1.1.0.0) revealed noteworthy coordination flexibility upon treatment with Pd II ions as it converted to the C i ‐ ( 4 ) and C s ‐symmetric [NNNC]‐coordinated bis‐Pd II complexes [10] …”
Section: Methodsmentioning
confidence: 99%
“… [8] [26]Dioxohexaphyrin(1.1.1.1.1.1) provides a remarkable [NNNO] coordination core, as illustrated by paramagnetic bis‐Cu II compound 3 (Scheme 1) or diamagnetic bis‐Ni II complexes [9] . Incorporation of a pyridine unit into the expanded porphyrin core can be expected to result in specific coordination behaviour [10–13] . Thus, C,G‐di‐pyri‐octaphyrin(1.1.0.0.1.1.0.0) revealed noteworthy coordination flexibility upon treatment with Pd II ions as it converted to the C i ‐ ( 4 ) and C s ‐symmetric [NNNC]‐coordinated bis‐Pd II complexes [10] …”
Section: Methodsmentioning
confidence: 99%
“…Replacing one or more pyrrole rings of porphyrinoids with other heterocycles such as furan, thiophene, selenophene, or tellurophene or carbacycles such as cyclopentadiene, benzene, or related aromatic rings resulted in core-modified porphyrinoids, which possess significantly altered electronic properties compared to porphyrinoids. Over the years, several types of core-modified porphyrinoids have been synthesized; their physico-chemical properties have been studied and their use has been explored for various applications. , In recent times, polyaromatic hydrocarbons such as biphenyl, naphthalene, anthracene, phenanthrene, fluorene, dibenzo­[ g , p ]­chrysene, and pyrene , have been incorporated in the porphyrinoid framework in place of one or more pyrrole rings and the resulting polyaromatic hydrocarbon (PAH)-embedded porphyrinoids exhibit quite different and unique structural, electronic, and coordination properties. Specially, PAH-embedded porphyrinoids are very useful to understand the fundamentals of aromaticity and the global versus local π-electron delocalization in macrocycles and are also used as ligands to form organometallic complexes .…”
Section: Introductionmentioning
confidence: 99%
“…Among expanded porphyrinoids, the benzene-containing expanded porphyrinoids in which one or more pyrrole(s) or other five-membered heterocycle(s) were replaced with the 1,3-phenylene or 1,4-phenylene moiety have attracted much attention because of their potential ability to form organometallic complexes with various metals . However, perusal of literature revealed that the reports on benzene-containing expanded porphyrinoids are limited, although interesting phenanthrene-embedded porphyrinoids have been reported. , To understand their physicochemical and coordination properties, more examples are required on benzene-containing expanded porphyrinoids.…”
Section: Introductionmentioning
confidence: 99%